Governance, Participation, and Policy in Urban Cooperative: Insights from a People-Centered Development Approach - Achmad Barlian; Dinda Maulina Pangestu; Hilka Agustina Maryamah; Bisma Widyawan (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2026)
This study explores how urban cooperatives contribute to people-centered economic development through the framework of Local Economic Development (LED). Using a qualitative approach within a post-positivist paradigm, it examines the case of Koperasi Merah Putih in Jakarta. The findings indicate that cooperative performance is shaped by governance, member participation, institutional backing, and local socio-economic conditions. Strong governance and active member engagement are linked to greater social equity and economic gains. However, bureaucratic barriers and limited policy coherence remain key challenges. The study highlights the need for context-specific strategies and collaborative governance to improve cooperative outcomes. It contributes to the discourse on cooperative-driven development by showing how participatory approaches can foster inclusive growth. Policy recommendations include targeted support, improved stakeholder coordination, and adaptive governance to strengthen urban cooperatives.